MULTIKULTURALISME PADA PENDIDIKAN ANAK USIA DINI - Novita Harini; Irfan Noor; M. Iqbal (CV. ADIBA AISHA AMIRA, 2025)
This article discusses the importance of multiculturalism in Early Childhood Education (ECE) as an effort to shape character and inclusive social values among children. With the increasing diversity of cultural, ethnic, and religious backgrounds in society, multicultural education has become crucial to address potential conflicts and prejudices arising from these differences. Through an educational approach that emphasizes the values of tolerance, democracy, equality, and justice, ECE can serve as a platform for teaching children the importance of respecting diversity. The method used in writing this article is library research, which involves gathering various references from books, journals, and studies related to ECE and multiculturalism. The research also highlights that the ages 0-6 are a golden period for instilling these values, given the rapid psychological and social development of children at this stage. Multicultural education not only focuses on religious and ethnic diversity but also covers social and economic aspects that influence children's experiences. By equipping children with positive understanding and experiences of diversity, it is hoped that they can grow into individuals who are open-minded and able to interact harmoniously in a pluralistic society. Overall, this article emphasizes that the implementation of multicultural education in ECE is not only beneficial for the individual development of children but also contributes to creating a more peaceful and respectful society in the future